Sustainability beyond the triple bottom line: evaluating transformative change in food systems - Gunton, Richard M.; van der Stoep, Jan; Araya, Yoseph; Jochemsen, Henk (Frontiers in Sustainable Food Systems, 2025)
The concept of ‘sustainability’ has developed into a rich discourse concerned with diverse human responsibilities in our economic life, and as such it is in constant danger of over-simplification. The conventional two-way analysis of sustainability, into (1) human needs as ends and (2) means to meet such needs, and the scheme of nine planetary boundaries, are taken as starting points for a more balanced proposal set out in this conceptual paper. Inspired by the framework of Doughnut Economics and drawing on a collection of recent articles in this journal, we identify a set of 12 aspects for evaluating transformative change and apply them to food systems: seven typically instrumental goods (means) and five typically final goods (ends). Recognising that such classifications are worldview-dependent, however, our ‘home model’ breaks down the 12 aspects into 37 criteria as the basis for a practical tool for evaluating particular business models and policy initiatives. The paper concludes by offering a philosophical account of transformative change and identifying institutional factors crucial for local progress towards sustainability transitions, in food systems and also more broadly.